Development of Proximal Junctional Kyphosis After Minimally Invasive Lateral Anterior Column Realignment for Adult Spinal Deformity. Issue 2 (28th March 2018) - Gandhi, Shashank V; Januszewski, Jacob; Bach, Konrad; Graham, Randall; Vivas, Andrew C; Paluzzi, Jason; Kanter, Adam; Okonkwo, David; Tempel, Zachary J; Agarwal, Nitin; Uribe, Juan S
Abstract: BACKGROUND: Development of proximal junctional kyphosis (PJK) after correction of adult spinal deformity (ASD) undermines sagittal alignment. Minimally invasive anterior column realignment (ACR) is a powerful tool for correction of ASD; however, long-term PJK rates are unknown. OBJECTIVE: To characterize PJK after utilization of ACR in ASD correction. METHODS: A retrospective multi-institution cohort analysis per STROBE criteria was conducted of all patients who underwent lateral lumbar interbody fusion (LLIF) or ACR for ASD from 2010 to 2015. All patients obtained preoperative and follow-up upright radiographs, assessing spinal alignment and development of PJK. Patients without proper imaging or minimum 1-yr follow-up were excluded. RESULTS: A total of 73 of 112 patients who underwent either LLIF or ACR for ASD met inclusion criteria. Mean follow-up was 22.8 mo. There was significant improvement of all spinopelvic parameters. Overall, PJK and proximal junctional failure (PJF) rates were 20.5% and 11%, respectively. The incidence of PJK increased with greater corrective surgery (0% LLIF, 30% ACR, 42.9% ACR + posterior column osteotomy (PCO); P < .001). PJF rates increased (0% LLIF, 11% ACR, 40% ACR + PCO; P = .005). Risk factors included location of the upper-instrumented vertebra at T10-L1 vs L2-L4 ( P = .007), age ( P = .029), severity of ASD, and overcorrection of sagittal imbalance. CONCLUSION: The incidence of PJK after minimally invasive ACR is slightly lower than reported after open surgery but greater than in LLIF only and increases with PCO utilization. The PJK rate increases when crossing the TL junction, sagittal imbalance severity, and overcorrection. Elderly patients are at an increased risk, suggesting need for age appropriate correction goals.